Condições de saúde de prematuros moderados e tardios no primeiro ano de vida - Jantsch, Leonardo Bigolin (2018)
Moderate and Late Prematurity (PMTMT), Gestational Age in the range of 32 weeks to 36 weeks and 6 days, represent high survival rates in health services. These preterm infants, considering the "near-term" late, and their demands for prematurity remain invisible to post-discharge hospital specialties. Thus, the objective is: To analyze the health conditions of moderate and late preterm infants in the first year of life. The Health Condition and Health Care Networks (RAS) were used as a conceptual framework. It is a mixed study, in the quantitative approach, characterized as an epidemiological study, longitudinal and in the qualitative, descriptive exploratory stage. In the quantitative stage, 151 PMTMT were followed in the initial analysis, with a percentage of 28% of losses at the end of the first year of follow-up. To collect the data, forms were applied, whose purpose was to evaluate the outcome for the development of chronic and acute health conditions in the study population. The monitoring instrument was applied by telephone, every three months, by the researchers, until the child completed one year of life. At the qualitative stage, we sought to know the construction of the health network of these premature infants through a semi-structured interview with 15 caregivers / relatives of premature infants who developed chronic and acute health conditions. Quantitative data were analyzed through analytical statistics and qualitative data through thematic content analysis. The study was approved by the ethics committee under opinion number 2.167.071: and followed the recommendations of resolution nº 466/2012. Of those born in the study hospital, 20% were PMTMT, 14% of whom had a Specific Health Care at the time of hospital discharge. At discharge, 99% of them were referred to some health service. The first contact of these preterm infants with the post-discharge health network was absent and disarticulated, causing a weak link and lack of follow-up in the health of this population. The prevalence of Chronic Health Condition was 20% to 12% of the PMTMT population during the first year of life, being significantly more frequent in moderates and with a higher prevalence in the third month of life. Acute injuries presented a linear trend throughout the first year of life. Gastrointestinal conditions were more intense in the first months and skin allergy and respiratory conditions more frequent at the end of the first year of life. The health follow-up network of these preterm infants presents in a fragmented way, being translated by the attendance of the acute affections in emergency and emergency services. Early access to Primary Health Care (PHC) is considered to be a decisive factor in the organization of PHC services, where PHC becomes the coordinator of care. We conclude that moderate and late preterm infants present habitual and specialized health demands, especially in the first months of life, which require an organized and articulated response from services.